Assessment of food supplementation and surveillance as techniques to reduce damage caused by black capuchin monkeys Sapajus nigritus to forest plantations. Issue 5 (1st October 2014) - Mikich, Sandra Bos; Liebsch, Dieter
Abstract: Black capuchin monkeys Sapajus nigritus are among several mammalian species that damage forest plantations, primarily plantations of pine trees ( Pinus spp.) in South Brazil. Management practices to reduce these damages include supplementary food offerings and plantation surveillance. To assess the efficiency of these techniques, four treatments were evaluated: feeding (F, with supplementary bananas and maize), surveillance (S, in situ, wherein men patrolled the plantations, deterring the monkeys), feeding + surveillance (FS) and control (no procedures) (C). The efficiency assessment of each treatment involved the number of recorded primate sightings in the treatments with the presence of guards (S and FS) and a damage inventory of the outskirts of the experimental points immediately before and after the experiment. These data were complemented by a simultaneous study of the availability of fruit, the primary item in the diet of this primate species, in the remnant native forest in the study area. Most sightings of S. nigritus occurred early in the morning, and in general, sightings were inversely proportional to the availability of native fruits. This trend was most evident in treatment FS, most likely due to the presence of food. Treatments F and FS exhibited higher percentages of damage, indicating that these are inefficient management techniques. Treatment S exhibited the lowest damage rate, but at a high cost, making this technique difficult to apply over large expanses. The development of other management techniques, such as environmental enrichment and the use of deterrents, is recommended to minimize the damage caused by capuchins in forest plantations.